2016
DOI: 10.5812/ircmj.36732
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bayesian Hierarchical Model for Detecting Effective Factors on Growth Failure of Infants Less Than Two Years of Age in a Multicenter Longitudinal Study

Abstract: BackgroundNowadays, one of the major public health problems among children is growth failure. It can be characterized in terms of either inadequate growth or the inability to maintain growth.ObjectivesThe main objective of this study was to examine the effects of some factors on growth failure among a sample of infants less than two years old.Materials and MethodsThe present longitudinal archival study relied on data gathered from health files from February 2007 to July 2010 for 1,358 children under two years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Consistent with findings from other DHS surveys, we did not find an association between the prevalence of wasting and household wealth quintile (Assaf & Pullum, ). Previous research has suggested that immediate factors, such as child feeding and care practices and prevalence of disease and inflammation, are drivers of child wasting and are mediating factors between socio‐economic status and child wasting (Fernandez, Himes, & de Onis, ; Zayeri et al, ). Agroecological zone was significantly associated with child stunting in Myanmar, with children in the mountainous upland states most likely to be stunted and children in the coastal zone more likely to be wasted, a finding that is in line with previous national and subnational surveys (LIFT, ; Ministry of National Planning and Economic Development & Ministry of Health, ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with findings from other DHS surveys, we did not find an association between the prevalence of wasting and household wealth quintile (Assaf & Pullum, ). Previous research has suggested that immediate factors, such as child feeding and care practices and prevalence of disease and inflammation, are drivers of child wasting and are mediating factors between socio‐economic status and child wasting (Fernandez, Himes, & de Onis, ; Zayeri et al, ). Agroecological zone was significantly associated with child stunting in Myanmar, with children in the mountainous upland states most likely to be stunted and children in the coastal zone more likely to be wasted, a finding that is in line with previous national and subnational surveys (LIFT, ; Ministry of National Planning and Economic Development & Ministry of Health, ).…”
Section: Discussionmentioning
confidence: 99%